Hydroxyl substituted benzoic acid/cinnamic acid derivatives: Tyrosinase inhibitory kinetics, anti-melanogenic activity and molecular docking studies. Issue 1 (1st January 2020) - Nazir, Yasir; Saeed, Aamer; Rafiq, Muhammad; Afzal, Samina; Ali, Anser; Latif, Muhammad; Zuegg, Johannes; Hussein, Waleed M.; Fercher, Christian; Barnard, Ross T.; Cooper, Matthew A.; Blaskovich, Mark A.T.; et al.
Graphical abstract: Abstract: The inhibition of tyrosinase is an established strategy for treating hyperpigmentation. Our previous findings demonstrated that cinnamic acid and benzoic acid scaffolds can be effective tyrosinase inhibitors with low toxicity. The hydroxyl substituted benzoic and cinnamic acid moieties of these precursors were incorporated into new chemotypes that displayed in vitro inhibitory effect against mushroom tyrosinase . The most active compound, (2-(3-methoxyphenoxy)-2-oxoethyl (E)-3-(4-hydroxyphenyl) acrylate) 6c, inhibited tyrosinase with an IC50 of 5.7 µM, while (2-(3-methoxyphenoxy)-2-oxoethyl 2, 4-dihydroxybenzoate) 4d had an IC50 of 23.8 µM. In comparison, the positive control, kojic acid showed tyrosinase inhibition with an IC50 = 16.7 µM. Analysis of enzyme kinetics revealed that 6c and 4d displayed noncompetitive reversible inhibition of the second tyrosinase enzymatic reaction with Ki values of 11 µM and 130 µM respectively. In silico docking studies with mushroom tyrosinase (PDB ID 2Y9X) predicted possible binding modes in the catalytic site for these active compounds. The phenolic para -hydroxy group of the most active compound 6c is predicted to interact with the catalytic site Cu ++ ion. The methoxy part of this compound is predicted to form a hydrogen bond with Arg 268. Compound 6c had no observable toxic effects on cell morphology or cell viability at the highest tested concentration of 91.4 µM. When dosed at 91.4 µM onto B16F10 melanoma cells in vitro 6c showed anti-melanogenic effects equivalent to kojic acid at 880 µM. 6c displayed no PAINS (pan-assay interference compounds) alerts. Our results show that compound 6c is a more potent tyrosinase inhibitor than kojic acid and is a candidate for further development. Our exposition of the details of the interactions between 6c and the catalytic pocket of tyrosinase provides a basis for rational design of additional potent inhibitors of tyrosinase, built on the cinnamic acid scaffold.